PENERAPAN MEDIA SNAKES AND LADDER UNTUK MENINGKATKAN HASIL BELAJAR(Studi kasus Peserta didik IX IPS A SMPN 53 SURABAYA) - Nur Naini, Irma; Katon Galih Setyawan; Sukarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the improvement in learning outcomes of class IX A students at SMPN 53 SURABAYA in social studies subjects. The research method used is classroom action research. And the research subjects were 32 students in class IX A of SMPN 53 SURABAYA. The learning outcomes of students in class IX A of SMPN 53 SURABAYA are still low because the majority of students have not reached the specified KKTP. The research results show that applying snakes and ladder media can improve the learning outcomes of class IX A students at SMPN 53 SURABAYA. This is proven by the increase in student learning outcomes from cycle I by 81%, increasing in cycle II to 94%. So it can be concluded that the application of Snakes and Ladder media in learning can improve the learning outcomes of class IX A students at SMPN 53 SURABAYA.